The Effect of Warm Compress Therapy in Reducing Headache Intensity and Stabilizing Blood Pressure in Hypertension Patients - Rohmawati, Dhian Luluh; Nisak, Raudhotun; Lukitaningtyas, Dika; Kartika, Kartika (GLOBAL HEALTH SCIENCE GROUP, 2024)
Hypertension is a global health concern, increasing annually. Headaches in hypertensive patients indicate high blood pressure levels, affecting brain blood vessels. These headaches should be promptly evaluated and treated for significant health risks. Objective: This study investigates the impact of warm compresses on headache and blood pressure reduction in hypertensive patients. Method: The study, conducted at a community health center in Ngawi Regency, focused on hypertension patients with headaches. The researchers used a one-group pretest posttest design and measured headache pain using the NRS scale before applying a warm compress. Data analysis for this study was conducted using the Wilcoxon Signed-Rank Test. Results: The research results show that the average pain level decreased by 1.18, indicating a significant difference before and after the application of a warm compress. This study also shows that the average systolic blood pressure decreased by 15.87, indicating a significant difference (p-value <0.05) before and after the application of a warm compress. Additionally, the average diastolic blood pressure decreased by 13.27, indicating a significant difference (p-value <0.05) before and after the intervention. Conclusions: there is a significant effect of warm compresses on headache pain and on lowering blood pressure in patients with hypertension.